1993
DOI: 10.1073/pnas.90.18.8586
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1 induces the transversion of G-->T in codon 249 of the p53 tumor suppressor gene in human hepatocytes.

Abstract: Hepatoceliular carcinoma (HCC) represents a major cause of mortality in certain areas ofthe world. Contamination offood with the mycotoxin aflatoxin B1 (AFB1) has been implicated as an etiological factor in certain regions of eastern Asia and subSaharan Africa (1, 2). Indeed, recent studies suggest that hepatitis B virus and AFB1 may exert a synergistic effect (3). Approximately 50%6 of HCC in high AFB1 regions (4, 5), but only 20%o in low AFB1 regions, harbors mutations in the p53 tumor suppressor gene, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
199
0
13

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 436 publications
(230 citation statements)
references
References 25 publications
18
199
0
13
Order By: Relevance
“…In vitro studies exposing human liver cell lines to AFB 1 presented the same 249 ser mutational pattern of TP53 (Aguilar et al, 1993;Mace et al, 1997), as it has been reported in the epidemiological studies ( Figure 1c). There are at least two possible explanations for these findings.…”
Section: Aflatoxin Bsupporting
confidence: 76%
See 1 more Smart Citation
“…In vitro studies exposing human liver cell lines to AFB 1 presented the same 249 ser mutational pattern of TP53 (Aguilar et al, 1993;Mace et al, 1997), as it has been reported in the epidemiological studies ( Figure 1c). There are at least two possible explanations for these findings.…”
Section: Aflatoxin Bsupporting
confidence: 76%
“…Aguilar et al (1994) have shown a higher relative abundance of the 249 ser mutant liver cells, in nontumorous liver, by using a highly sensitive genotypic mutation assay. They suggested that this early mutational event may be due to the high mutability of the third base at codon 249 to AFB 1 , as suggested by previous in vitro studies in human liver cells (Aguilar et al, 1993;Cerutti et al, 1994). Another possible explanation might be that the 249 ser mutant p53 protein may provide a special growth and/or survival advantage to these liver cells (Puisieux et al, 1995).…”
Section: Aflatoxin Bmentioning
confidence: 80%
“…Rat liver microsome-activated AFB1 preferentially induces the transversion of G=ϾT in the third position of codon 249 in human HCC cells (HepG2). 36 However, AFB1 also induces G=T and C=A transversions into adjacent codons, albeit at lower frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Dimethylbenzanthracene (DMBA) causes primarily base pair substitutions, predominantly A:T 3 T:A (44%) and G:C 3 T:A (24%) [Manjanatha et al, 2000]. In human populations, signature mutations associated with specific exogenous mutagens have been observed in samples of somatic mutations in the p53 tumor-suppressor gene [Harris and Hollstein, 1993;Hussain and Harris, 1999], for example, G 3 T transversions in lung cancers of cigarette smokers [Chiba et al, 1990], C 3 T and CC 3 TT tandem dipyrimidine transitions in skin cancers associated with excessive sun exposure [Brash et al, 1991], and G 3 T transversions at arginine 249 in liver cancers associated with aflatoxin exposure [Bressac et al, 1991;Hsu et al, 1991;Scorsone et al, 1992;Aguilar et al, 1993;Li et al, 1993]. Such signature mutations can be detected in the mutation pattern with high sensitivity.…”
Section: Signature Mutations Permit Identification Of Mutagensmentioning
confidence: 99%